Female in Leadership Roles: The Experience of Female School Principals from Two Secondary Schools in South Sumatra - Pratama, Andika Putra; Amrullah, Amrullah; Vianty, Machdalena (Indonesian Research Journal in Education |IRJE|, 2024)
In the Indonesian school contexts, the female elementary and secondary school teachers outnumber their male counterparts. However, it is a different story when it comes to school leadership. Therefore, investigating school leadership from the point of view of female school principals is worth doing and this was the aim of this present study. Involving two female secondary school principals as the main participants of study, this present study investigated the participants’ experience of the challenges as school principals and what strategies and recommendation the participants had to overcome the challenges. The data were obtained through semi-structured interviews and were analysed by using thematic analysis. The results of this study showed that the challenges of the participants encountered in leadership position were subtle discrimination in the form of negative perception before carrying out the roles as principals, resistance from senior staff, family views on career, balance between work and family, obstacle from family, adapting ICT in education, and age-related barriers to technology. To responds to the challenges, the participants did the mentorship and networking program, clear vision and communication, having dialogue about career goals and family responsibilities, setting clear boundaries expectations, involving family in decisions making, provide ongoing ICT training for educators, mentorship programs for technology integration.  The findings of this present study contribute to the field of female leadership in education by providing information about what the Indonesian female school principals in leadership position and as a school leader.